THE EFFECT OF FOOD SANITATION ON PUBLIC NUTRITIONAL HEALTH - Dita Hasni; Wilham Sevy Ramadhan; Andika Cafriarsida; Budi Yulhasfi Febrianto (Yayasan Nusantara Hasana Berdikari, 2023)
Motivation/Background: Food is a fundamental necessity for human life. If the meaning consumed is not good or expired, it will cause food poisoning. Cases of food poisoning and foodborne infectious diseases are common. One of the causes is not paying attention to the sanitation of the food. Therefore, good or bad food sanitation will greatly affect the health of the community. This study aims to analyze how much influence food sanitation has and also the impact of food sanitation on public nutrition health Method: The method used is a literature study by reviewing several journals related to the effect of food sanitation on public nutritional health. Article search using one database, namely Google Scholar. Results: Based on search results through Google Scholar and journals that have been identified, there are 10 full-text journals and according to eligibility. The 10 journals are in accordance with inclusion criteria that focus on discussing the effect of food sanitation on public nutritional health. Conclusions: the better food sanitation efforts are carried out, the better the nutritional health of the community.